2021 IEEE International Symposium on Circuits and Systems (ISCAS) 2021
DOI: 10.1109/iscas51556.2021.9401766
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of EEG Datasets for Epileptic Seizure Prediction

Abstract: This paper provides a comprehensive analysis of the available EEG datasets that are used for epilepsy prediction systems, including Melbourne, CHB-MIT, American Epilepsy Society, Bonn, and European Epilepsy datasets. These datasets are compared in terms of the sampling rate, number of patients, recording time, number of channels, artifacts, and types of EEG signals. We also provide details on the challenges of using one dataset over the others in predicting epilepsy. Subsequently, we compare the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The subjects are two humans and five canines with channels from 15 to 24 per subject. The EEG recordings include a line noise of 60 Hz that could be fixed using a notch filter [34].…”
Section: American Epilepsy Society Datasetmentioning
confidence: 99%
“…The subjects are two humans and five canines with channels from 15 to 24 per subject. The EEG recordings include a line noise of 60 Hz that could be fixed using a notch filter [34].…”
Section: American Epilepsy Society Datasetmentioning
confidence: 99%
“…Compared with other brain imaging methods, EEG has the advantages of non-invasive, high temporal resolution and convenient detection [5] . In clinical, EEG is mainly used in epilepsy detection [6] , sleep detection [7] and so on. In addition, studies have shown that EEG Event-related potential (ERP) induced by acoustic stimulation can be used as biomarkers for hearing assessment [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Epilepsy is one of the most common neurological disorders in humans, affecting approximately 60 million people worldwide who are unable to live normally [ 1 ]. Approximately 70–80% of epilepsy patients are well controlled with medication or surgery, but about 20–30% of patients are still not effectively treated [ 2 ].…”
Section: Introductionmentioning
confidence: 99%